DEVELOPING CRITICAL INTERCULTURAL COMPETENCE IN SECOND LANGUAGE TEACHER EDUCATION - Yaprak, Zeynep; Özmen, Kemal Sinan (International Online Journal of Education and Teaching, 2021)
This study aims to explore the impact of critical thinking skills on the promotion of intercultural competence in language classrooms. Participants in this study were 34 student teachers studying English Language Teaching. The statistical analysis of data was carried out by using SPSS. Additionally, in order to see the magnitude of the impact of the training, the statistical differences between experimental and the control groups were confirmed with appropriate effect size calculations. According to statistical analysis and student teachers’ reflections, critical thinking skills played a complementary and crucial role in fostering intercultural knowledge, awareness, and sensitivity.